Kesejahteraan di Balik Rempah: Analisis Determinan Ekonomi Rumah Tangga Petani Pala Fakfak - Arga Ramadhana; Rumasukun, Hasim; Kuliahsari, Dessy Eka (Jurnal Informasi, Sains dan Teknologi, 2025)
Indonesia is an agrarian country endowed with abundant natural resources, vast agricultural land, rich biodiversity, and a tropical climate that supports the development of the agricultural sector. One of the leading plantation commodities in West Papua Province is nutmeg, which is widely cultivated in the regions of Fakfak, Kaimana, and Teluk Bintuni. This study aims to analyze the influence of land area, education level, number of household members, and income on the welfare of nutmeg farming households, both partially and simultaneously. The research was conducted in Kampung Sekru, Pariwari District, Fakfak Regency, West Papua, where most of the population depends on nutmeg farming as their main livelihood. The analytical method used is multiple linear regression with the assistance of SPSS software, which includes the t-test, F-test, and coefficient of determination (R²). The findings show that partially, land area (X₁) with a significance value of 0.0573 and number of household members (X₃) with a significance of 0.0811 have no significant effect on household welfare (p > 0.05). In contrast, education level (X₂) with a significance value of 0.033 and income (X₄) with a significance of 0.001 show a significant effect (p < 0.05). Simultaneously, the F-test results indicate a significance value of 0.000 (p < 0.05), confirming that all independent variables together significantly affect the welfare of nutmeg farming households in Kampung Sekru.